2011
DOI: 10.1089/jmf.2010.1027
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of SG-168 Against Oxidative Stress-Induced Apoptosis in PC12 Cells

Abstract: Postmortem examinations of tissues of humans and rodents with a host of neurodegenerative conditions, including Alzheimer's and Parkinson's diseases, have identified oxidative damage in proteins, lipids, and DNA. The aim of this study was to better understand the cellular mechanisms of neuronal cell degeneration induced via oxidative stress and the protective roles of bioactive substance. In order to achieve this aim, we established a screening program to discover therapeutic agents that exhibit preferential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In an earlier study, Chan et al (2009) reported that the antioxidant and neuroprotective role of astaxanthin and canthaxanthin protected the differentiated PC12 cells from H 2 O 2 -induced cell death, LDH leakage, DNA fragmentation, mitochondrial membrane damage, lipid peroxidation, glutathione depletion and antioxidant enzyme status. Similarly neuro and lung protective property of various novel compounds have been established by many researchers (Gao et al 2010;Lu et al 2010;Shen et al 2011;Liu et al 2011;Yoon et al 2011;Luo et al 2011). In the same way the present results are in support with earlier studies suggesting neuro and lung protective propensity of BME.…”
Section: Discussionmentioning
confidence: 96%
“…In an earlier study, Chan et al (2009) reported that the antioxidant and neuroprotective role of astaxanthin and canthaxanthin protected the differentiated PC12 cells from H 2 O 2 -induced cell death, LDH leakage, DNA fragmentation, mitochondrial membrane damage, lipid peroxidation, glutathione depletion and antioxidant enzyme status. Similarly neuro and lung protective property of various novel compounds have been established by many researchers (Gao et al 2010;Lu et al 2010;Shen et al 2011;Liu et al 2011;Yoon et al 2011;Luo et al 2011). In the same way the present results are in support with earlier studies suggesting neuro and lung protective propensity of BME.…”
Section: Discussionmentioning
confidence: 96%
“…(Orchidaceae) has been used in Traditional Chinese Medicine (TCM) and as an herbal medicine in many Asian countries for hundreds of years with special pharmacological effects on gastritis, diabetes, cancer and ageing 1–4 . It has been officially listed as “Shi Hu” in different versions of the Pharmacopoeia of the People’s Republic of China.…”
Section: Introductionmentioning
confidence: 99%
“…In ancient Chinese medical literature dating back over a thousand years, Dendrobium extracts were reported to improve vision [11]; however, there is still no firm understanding of the chemical components and mechanism of these extracts on vision. Recent research indicates that Dendrobium extracts may also have other bioactive properties, including the induction of apoptosis in human gastric cancer cells [12], the facilitation of neuroprotection against stress-induced apoptosis in PC12 cells [13], the inhibition of lipopolysaccharide- (LPS-) induced memory impairment in rats [14], and the LPS-induced nitric oxide production in macrophages [15]. It has also been suggested that Dendrobium extracts have strong antioxidant properties in vitro [16].…”
Section: Introductionmentioning
confidence: 99%